PENERAPAN MODEL PROBLEM BASED LEARNING MELALUI APLIKASI WHATSAPP GROUP DALAM PEMBELAJARAN BIOLOGI UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA - I GEDE PUTU SUARDIKA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This classroom action research aims to improve the learning outcomes and activities of students of class X MIPA 3 SMA Negeri 1 Mangosteen in the even semester of the 2020/2021 school year through the application of a problem based learning model. This research was conducted in two learning cycles. The object of research is in the form of learning outcomes and student activities. To measure student learning outcomes, a test of student learning outcomes is used in the form of 25 objective questions. To measure student activity, a student activity observation sheet was used which contained 5 items of observed activity and used a linkert scale scoring guideline. The data analysis used in this study was descriptive analysis. The results showed that the application of the problem based learning model through the whatsapp group application in biology learning could improve the learning outcomes and activities of class X MIPA 3 students at SMA Negeri 1 Manggis in the even semester of the 2020/2021 school year. Based on the results of the analysis of the provision of action that student learning outcomes in the first cycle of 75.4 increased by 4.6% to 80 in the second cycle. The absorption of learning outcomes in the first cycle of 75% increased to 80% in the second cycle. Classical completeness in the first cycle of 86% increased to 94% in the second cycle. This achievement is in accordance with the criteria for which research success has been determined, namely an average learning outcome of at least 65, absorption of at least 65% and classical completeness of at least 85%. The activities of class X MIPA 3 students of SMA Negeri 1 Manggis in the even semester of the 2020/2021 school year can be increased through the application of problem based learning models in biology learning. Achievement of student activities continues to increase up to 78% of students who at least have very active activities. This achievement is in accordance with the criteria that the success of the research has determined, namely the number of students having active activities of at least 85%. The application of the problem based learning model in biology learning can improve student learning outcomes and activities, so this research can be continued by other researchers by raising different subjects and objects. ABSTRAKPenelitian tindakan kelas ini bertujuan untuk meningkatkan hasil belajar dan aktivitas siswa kelas X MIPA 3 SMA Negeri 1 manggis semester genap tahun pelajaran 2020/2021 melalui penerapan model problem based learning. Penelitian ini dilakukan dalam dua siklus pembelajaran. Obyek penelitian berupa hasil belajar dan aktivitas siswa. Untuk mengukur hasil belajar siswa digunakan tes hasil belajar siswa yang berbentuk soal obyekstif sebanyak 25 butir soal.Untuk mengukur aktivitas siswa digunakan lembar observasi aktivitas siswa yang berisikan 5 butir aktivitas yang diamati dan menggunakan pedoman penskoran skala linkert.Analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif. Hasil penelitian menunjukkan penerapan model problem based learning melalui aplikasi whatsapp group dalam pembelajaran biologi dapat meningkatkan hasil belajar dan aktivitas siswa kelas X MIPA 3 SMA Negeri 1 Manggis semester genap tahun pelajaran 2020/2021. Berdasarkan hasil analisis pemberian tindakan bahwa hasil belajar siswa pada siklus I sebesar 75,4 meningkat sebesar 4,6% menjadi 80 pada siklus II. Daya serap hasil belajar siklus I sebesar 75% meningkat menjadi 80% pada siklus II. Ketuntasan klasikal pada siklus I sebesar 86% meningkat menjadi 94% pada siklus II. Capaian ini sesuai dengan kriteria yang keberhasilan penelitian ditetapkan yaitu rata-rata hasil belajar minimal 65, daya serap minimal 65% dan ketuntasan klasikal minimal 85%. Aktivitas siswa kelas X MIPA 3 SMA Negeri 1 Manggis pada semester genap tahun pelajaran 2020/2021 dapat ditingkatkan melalui penerapan model problem based learning dalam pembelajaran biologi. Pencapaian aktivitas siswa terus mengalami peningkatan hingga 78% siswa yang minimal memiliki aktivitas sangat aktif. Capaian ini sesuai dengan kriteria yang keberhasilan penelitian ditetapkan yaitu jumlah siswa memiliki aktivitas aktif minimal 85%.Penerapan model problem based learning dalam pembelajaran biologi dapat meningkatkan hasil belajar dan aktivitas siswa, sehingga penelitian ini dapat dilanjutkan oleh peneliti lain dengan mengangkat subjek dan objek yang berbeda.